Optimization of Antibacterial Efficacy of Eucalyptus and Lemon Essential Oils in Hand Sanitizer with Simplex Lattice Design - Muhammad Fariez Kurniawan; Revitha Nova Salsabila (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2025)
Hand sanitizer spray is a spray kind of hand sanitizer that contains active antibacterial chemicals to eliminate germs on hands. Eucalyptus globulus essential oil contains antimicrobial properties, specifically Eucalyptol (50-65%). Citrus limon essential oil exhibits antibacterial properties due to its primary component, limonene (59.7%), which damages bacterial cell walls and inhibits bacterial enzyme activity. This study aimed to assess the impact of a hand sanitizer spray containing a combination of Eucalyptus globulus essential oil and Citrus limon essential oil on the physical properties of the product, evaluate its antibacterial activity against Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli, and identify the most effective formula using the Simplex Lattice Design method. The study employed the Simplex Lattice Design approach to compare the effects of Eucalyptus globulus essential oil and Citrus limon essential oil in hand sanitizer spray formulations with ratios of 100% : 0%, 0%: 100%, and 50%: 50%. Every formula underwent physical pH, homogeneity, and viscosity tests. Antibacterial testing was conducted on Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli microorganisms—a method for testing antibacterial activity by paper disc diffusion. The ideal formula was determined by Simplex Lattice Design calculations, resulting in a blend of 70% Eucalyptus globulus essential oil and 30% Citrus limon essential oil. The hand sanitizer spray preparations were tested for antibacterial properties on Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli bacteria. The average inhibition zones were 17.33 ± 0.67 mm, 13.33 ± 0.57 mm, and 21.2 ± 4.75 mm, respectively. The preparation exhibits pseudoplastic flow behavior and has a pH of 5.5.